2006
DOI: 10.1021/ol062540s
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthetic Approach to 2,4-Disubstituted Quinazolines

Abstract: [reaction: see text] 2,4-Dialkyl or aryl quinazolines have been prepared in three steps starting from easily available anilides. A photochemically induced Fries rearrangement of the anilides gave several ortho-aminoacylbenzene derivatives that were acylated at the NH2. These acylamides underwent rapid cyclization to 2,4-disubstituted quinazolines (and benzoquinazolines) in the presence of ammonium formate under microwave activation. This procedure is compatible with different functional groups and allowed also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…For instance, in Bischler cyclization [44-46], the most traditional synthetic methods for quinazoline derivatives, high temperature (above 120°C) and high pressure are needed for at least 5 h in saturated ammonia alcohol solution. Various synthesis applying this method contains the passage of ammonia through a mixed melt of the amino compound and sodium acetate at a temperature higher than 160°C [47], in which ultrasonic promotion is demanded.…”
Section: Reviewmentioning
confidence: 99%
“…For instance, in Bischler cyclization [44-46], the most traditional synthetic methods for quinazoline derivatives, high temperature (above 120°C) and high pressure are needed for at least 5 h in saturated ammonia alcohol solution. Various synthesis applying this method contains the passage of ammonia through a mixed melt of the amino compound and sodium acetate at a temperature higher than 160°C [47], in which ultrasonic promotion is demanded.…”
Section: Reviewmentioning
confidence: 99%
“…The key intermediates for this synthesis were easily obtained through green procedures. On the one hand, 2-aminobenzamide (190) reacted under MW-activation with chloroacetylchloride (191) to afford N-(2-aminophenyl)-2-chloroacetamide, an intermediate which could be cyclized into 2-chloromethylquinazoline-4(3H)-one (192) In the last decade, numerous syntheses of highly functionalized series of quinazoline derivatives have been described in the literature [187][188][189][190][191][192][193][194][195][196][197][198][199]. Kabri et al [187] reported several studies devoted to the synthesis of 2-substituted quinazolines (Scheme 40).…”
Section: Scheme 39mentioning
confidence: 99%
“…The key intermediates for this synthesis were easily obtained through green procedures. On the one hand, 2-aminobenzamide (190) reacted under MW-activation with chloroacetylchloride (191) These key intermediates 194 have been functionalized at position 2 according to different green procedures. On the one hand, these derivatives have been submitted to S-alkylations using sodium salts of various benzenesulfinic acid as alkylating agents.…”
Section: Scheme 39mentioning
confidence: 99%
“…The most recent convenient synthetic approach to 2,4-disubstituted quinazolines was published by Taddei and coworkers [14]. 2,4-Dialkyl or aryl quinazolines were prepared in three steps starting from easily available anilines.…”
Section: 4-di-substituted Quinazolinesmentioning
confidence: 99%